Self prestressing concrete composite with shape memory alloy. (2021) - Geetha, S.; Selvakumar, M.
Abstract: The infrastructure sector along with developing new ideology for constructing new facilities have equal importance in maintain the existing structure in making them serve the intended use for which it has been designed over the design period. In this context retrofitting of structures plays a major role in reviving the strength of the structural members. There are various methods used in the retrofitting process. But mainly they are passive strengthening techniques. Active technique like prestressing is costly. The use of Shape memory Alloy (SMA) has proved to be a boon to the civil engineers in improving the flexural strength of the existing beams. This paper discusses the test results of using Fe alloy as SMA for retrofitting beam. It has been noted that the FE alloy SMA when thermo mechanically treated improves the load carrying capacity by 60% and a self prestressing force is induced due the activation of the Fe alloy SMA. The mid span deflection and ultimate load carrying capacity has proved invariably by the use of this SMA.